PENGEMBANGAN MEDIA SMART BOX MATEMATIKA DALAM MENINGKATKAN KOGNITIF SISWA PADA MATERI PERKALIAN DI KELAS II SD - Salsabila, Rifda Zulvia; Yuhana, Yuyu; Alamsyah, Trian Pamungkas (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
An engaging learning medium can increase students’ interest and enthusiasm, especially in mathematics learning, where interactive media are essential to encourage active participation. This development research aims to investigate teachers’ use of media, the process of developing instructional media, the feasibility of the product, students’ cognitive improvement, and their responses toward the use of the medium. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The findings revealed that the Smart Box Mathematics media had never been used by teachers due to limited creative ideas, thus requiring collaboration in its creation. The media was rated as “Highly Feasible” with an average validation score of 89% from media experts, 93% from material experts, and a 94.66% positive response from students. Moreover, the cognitive understanding of students improved significantly, with an average N-Gain score of 82.2%, categorized as “Effective.” Therefore, the Smart Box Mathematics media for multiplication material in grade II elementary school is highly feasible and effective to support classroom learning.